Effects of residual stresses on fatigue crack propagation of an orthotropic steel bridge deck. (15th January 2021) - van den Berg, Niels; Xin, Haohui; Veljkovic, Milan
Abstract: Orthotropic steel decks (OSD's) are susceptible to fatigue failure due to cyclic loading. Often fatigue cracks are found in the joint between the deck plate and the trough. Due to the welding process, residual stresses are present in and around the joint. In this paper, the effect of residual stresses on the fatigue crack propagation rate has been evaluated. First, a FE model has been made to predict and validate the residual stress field of the OSD due to welding. The validation of residual stresses is made comparing measured data at the surface of the OSD and over the thickness of the deck flange. The residual stresses are used to subsequently model for a crack propagation analysis based on extended finite element method (XFEM). The fatigue crack simulation including residual stress field shows good correlation compared to the experimental data, while the simulation without residual stress field shows less correlation. The effects of the residual stresses are relatively large as the tensile transversal residual stresses increase the crack propagation, while the tensile longitudinal residual stresses decrease the crack propagation rate. The optimal modelling of the component of residual stresses is investigated. Graphical abstract: Unlabelled Image Highlights: A FE model including shrinkage due to welding has been made to predict and validate the residual stress field of the OSD. The fatigue crack simulation including residual stress field shows good correlation compared to the experimental data, while the simulation without residual stress field shows less correlation. The effects of the residual stresses are relatively large as the tensile transversal residual stresses increase the crack propagation, while the tensile longitudinal residual stresses decrease the crack propagation rate.